STUDY OF ENERGY BAND GAP IN NANO ZnO STRUCTURE FROM REFLECTANCE PATTERNS: STUDI BAND GAP ENERGI STRUKTUR NANO ZnO DARI POLA REFLEKTANSI - Syeha Lutfiah; Iwan Sugihartono; Rahmat Setiawan Mohar; Isnaeni; Maykel Manawan (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2025)
Nanostructured Zinc Oxide (ZnO) has been successfully synthesized using hydrothermal method. All precursors were mixed and stirred using an ultrasonic cleaner for 10 minutes until the sample was homogeneously mixed. Then, the samples were put into a Teflon-coated stainless steel autoclave and heated at 100ºC for 6 hours. Characterization of the optical properties of ZnO nanoparticles was carried out using UV-Vis Diffuse Reflectance spectrophotometer test. Furthermore, the optical properties will be analyzed referring to the reflectance pattern so that the band gap energy of ZnO nanoparticles can be determined using the Tauc Plot technique. The results of Tauc Plot analysis show that the band gap energy of ZnO nanoparticles is at 2.97 eV.